The Sustainability of Cement Mortar with Raw Sewage Sludge and Rice Husk Ash - Rawa Shakir Muwashee (Salehan Institute of Higher Education, 2020)
This study devotes to investigate the use of Raw Sewage Sludge (RSS) and Rice Husk Ash (RHA) to obtain sustainable construction materials. This study focuses on the evaluation of using cement-based materials having RSS and RHA. The methodology of this study could be summarized by replacing water by RSS and replacement of 10 %RHA from the weight of cement. Five groups have been used with different ratios of RSS/binder; for each group with and without RHA. In addition, the sand/binder ratio has been changed for Group 2. This method includes testing the flowability, compressive strength, Total Water Absorption (TWA) and density for the mortar mixes containing these materials. The results indicate that mixes with added materials encourage the results compared to control mixes. Addition of RHA considerably decreases flowability; however it enhanced compressive strength for all groups especially for Groups 3, 4 and 5. Moreover, the minimum values of TWA were recorded when 10% RHA was utilized as a cement replacement for both RSS and water mixes. Finally, it was found that replacing RSS by water, leads to the reduction in flowability and TWA in all mixes especially at 10% RHA; whereas the strength and density increase.